PEDAGOGICAL AND PSYCHOLOGICAL ASPECTS OF USING ETHICAL DILEMMAS IN DEVELOPING SANOGENIC REFLECTION - Ismailov Murodulla Kaxramonovich (International Journal of Literature and Language Studies, 2026)
This article analyzes the pedagogical and psychological aspects of using ethical dilemmas in developing sanogenic reflection in students. In modern higher education, the formation of a professionally competent and morally responsible personality requires not only theoretical knowledge and practical skills, but also the ability to make conscious decisions in complex situations, regulate emotional reactions, understand personal values, and reflect constructively on one’s own behavior. In this context, sanogenic reflection is considered an important psychological and pedagogical mechanism that helps students analyze their thoughts, emotions, motives, and actions in a healthy, constructive, and development-oriented way.